Electrical Characteristic Analysis of Photovoltaic Thermal With And Without ∇-Groove Absorber - Saprizal Hadisaputra; Muhammad Zohri; Ahmad Fudholi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The photovoltaic thermal (PVT) system is an up-and-coming renewable energy technology that simultaneously produces thermal and electrical energy. The objective of this paper is to improve the electrical efficiency of the photovoltaic thermal system with and without ∇-groove absorber. This study is an experimental investigation under an indoor solar simulator at The National University of Malaysia. The electrical characteristic of the PVT system is characterized by the scheming current (A), voltage (V), power (W) curves. The solar intensity and mass flow rate affected the electrical characteristic. The increase of produced power and electrical efficiency is caused by increasing the solar intensity and mass flow rate. The comparison between ∇-groove absorber and without ∇-groove absorber shows that the use of ∇-absorber can increase electrical efficiency.